2016
DOI: 10.1101/lm.039941.115
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of protein phosphatases in the destabilization of methamphetamine-associated contextual memory

Abstract: Destabilization refers to a memory that becomes unstable when reactivated and is susceptible to disruption by amnestic agents. Here we delineated the cellular mechanism underlying the destabilization of drug memory. Mice were conditioned with methamphetamine (MeAM) for 3 d, and drug memory was assessed with a conditioned place preference (CPP) protocol. Anisomycin (ANI) was administered 60 min after the CPP retrieval to disrupt reconsolidation. We found that destabilization of MeAM CPP after the application of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…While there is relatively little understanding of the neurochemical mechanisms of memory destabilization, several processes have been identified [101]. At the intracellular level, there appears to be a requirement for protein degradation at the proteasome [102, 103], protein phosphatase activity [104], CamKII [105] and nitric oxide [106, 107]. At the cell surface, there is a functional involvement of cholinergic [108] and dopaminergic receptors [109], at least for non-fear memory destabilization.…”
Section: The Reliability Of Reconsolidation Effectsmentioning
confidence: 99%
“…While there is relatively little understanding of the neurochemical mechanisms of memory destabilization, several processes have been identified [101]. At the intracellular level, there appears to be a requirement for protein degradation at the proteasome [102, 103], protein phosphatase activity [104], CamKII [105] and nitric oxide [106, 107]. At the cell surface, there is a functional involvement of cholinergic [108] and dopaminergic receptors [109], at least for non-fear memory destabilization.…”
Section: The Reliability Of Reconsolidation Effectsmentioning
confidence: 99%
“…Concordant with the hypothesis that L-LTP is the neural correlate of LTM, the temporary post-reactivation vulnerability of LTM to PSI infusion can be explained as destabilization of L-LTP, followed by a restabilization phase that requires protein synthesis, hence the susceptibility to PSI. The destabilization has been shown to require the activity of NMDA receptors [ 29 ], and to depend critically on endocytosis of GluA2-containing AMPARs [ 57 , 63 ].…”
Section: Introductionmentioning
confidence: 99%
“…This required downstream activation of protein phosphatase 1 (PP1) by calcineurin; inhibition of either of these phosphatases prevented destabilization and protected against amnesia. Yu et al (2016) also observed a reduction in AMPAR:NMDAR ratio following destabilization, and suggest that destabilization may be causally linked to internalization of AMPARs. Consistent with this view, Yu et al (2013) found that preventing AMPAR endocytosis with the interfering peptide Tat-Glu2 3γ prevented destabilization of methamphetamine context memory.…”
Section: Protein Phosphorylationmentioning
confidence: 74%
“…This is potentially problematic as different subtypes of NMDAR are differentially involved in the destabilization and restabilization of memories, so prereactivation administration may have an impact on memory destabilization mechanisms. Findings from fear memory reconsolidation indicating a double dissociation in the requirement for GluN2B-and GluN2A-containing NMDARs for memory destabilization and restabilization, respectively (Ben Mamou et al 2006;Milton et al 2013) have subsequently been supported in studies of drug memory reconsolidation, with GluN2B-containing NMDARs mediating the destabilization of methamphetamine-associated memories (Yu et al 2016) and GluN2A-containing NMDARs being critical for the restabilization of drug memories following reactivation (Wells et al 2016;Hafenbreidel et al 2017). Since memory destabilization is also blocked by antagonism at NMDARs it may be that memantine prevented reconsolidation from taking place-indeed the protective effect of memantine on memory, and slow kinetics, is what makes it attractive as a treatment option for Alzheimer's disease.…”
Section: Nmdar Antagonismmentioning
confidence: 93%
See 1 more Smart Citation